Surface display of lanmodulin protein on Escherichia coli for selective and efficient recovery of rare earth elements from bioleaching–leachate of ion−adsorption rare earth ore - Zebin Han; Zhu Chen; Guanzhou Qiu; Li Shen; Hongbo Zhao (Journal of Environmental Chemical Engineering, 2026)

Developmental toxicity of carboxylated microplastics in zebrafish mediated by mitochondrial dysfunction and inflammatory activation - Yantong Li; Yuyang Ni; Chenyin Dong; Jiayi Zhang; Hongzhi Guo; Shiyin Zhu; Chaoyi Du; Qi Yu; Zebin Wei; Yajing Han; Shaolin Xie (Environmental Pollution, 2026)

Seawater intrusion causes substantial release of dissolved organic carbon in coastal paddy soils - Wenting Chi; Yang Yang; Pei Wang; Chao Guo; Zebin Hong; Shiwen Hu; Kuan Cheng; Shan Wang; Han Li; Qi Wang; Ying Li; Yang Wu; et al. (Geochimica et Cosmochimica Acta, 2025)

Seasonal dynamics of ammonia-oxidizing archaea and bacteria in subalpine forests of western Sichuan - Li Zhang; Su Chen; Zebin Jiao; Sining Liu; Wenlan Huang; Lulu Huang; Liyun Yu; Lixia Wang; Bo Tan; Hongwei Xu; Lin Xu; Chengming You; et al. (Plant and Soil, 2025)

Activation of the CNGC2–CNGC4 channel complex by P2K1-mediated phosphorylation links extracellular ATP perception to calcium signaling in plant immunity - Yujia Sun; Lei Gao; Yiping Han; Changxin Feng; Zebin Liu; Chunyan Li; Yuxin Dong; Shuxin Yin; Laihao Liu; Ming Yang; Qi Niu; Dongdong Kong; et al. (Molecular Plant, 2025)

Bioleaching of rare earth elements from ores and waste materials: Current status, economic viability and future prospects - Zhu Chen; Zebin Han; Binyuan Gao; Hongbo Zhao; Guanzhou Qiu; Li Shen (Journal of Environmental Management, 2024)

Lactobacillus pentosus enabled bioleaching of red mud at high pulp density and simultaneous production of lactic acid without supplementation of neutralizers - Zebin Han; Binyuan Gao; Haina Cheng; Hongbo Zhou; Yuguang Wang; Zhu Chen (Journal of Environmental Chemical Engineering, 2024)

Vacancy engineering-induced spin polarization in heterogeneous phosphides by simple iron salt infiltration for efficient overall water splitting - Xuanning Qin; Zebin Yu; Zimu Zhang; Zuoyu Qin; Han Pang; Boge Zhang; Yanping Hou; Jun Huang; Ronghua Jiang; Jiayi Qu (Chemical Engineering Journal, 2024)

Treating waste with waste: Lignin acting as both an effective bactericide and passivator to prevent acid mine drainage formation at the source - Binyuan Gao; Zebin Han; Haina Cheng; Hongbo Zhou; Yuguang Wang; Zhu Chen (Science of The Total Environment, 2024)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Natural revegetation has dominated annual runoff reduction since the Grain for Green Program began in the Jing River Basin, Northwest China - Yipeng Yu; Pengtao Yu; Yanhui Wang; Yanfang Wan; Bin Wang; Xinsheng Han; Xinwu Tu; Jiamei Li; Lihong Xu; Xiao Wang; Zebin Liu (Journal of Hydrology, 2023)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Activity of the Lenglongling fault system and seismotectonics of the 2016 M S6.4 Menyuan earthquake - Peng Guo; ZhuJun Han; YanFen An; WenLiang Jiang; ZeBin Mao; Wei Feng (Science China Earth Sciences, 2017)